A “House United” or a “House Divided”: Investigating the Role of China’s Household Registration in Educational Quality and Equity in (Asian Education Studies, 2017)
The household registration system and policies have profound influences on the economic development, social transformation, and the process of urbanization and industrialization in China. This research paper conducted an extend review on China’s household registration policy’s influences on rural-to-urban migrant students’ educational participation, attainment, and achievement in K12 levels. Previous review of academic achievement gaps between rural-urban and migrant-local students identifies the quest for educational equity for every student, but much of them leave open the question of the historically rooted Hukou system’s powerful influences on migrant students’ educational experiences and outcomes in their processes of integration to the new social and cultural environment.